ANALISIS DEIKSIS PADA NOVEL SANG PEMIMPI KARYA ANDREA HIRATA - Aslina Aci (sarasvati, 2019)
This study attempts to describe deiksis, persona deiksis, place deiksis, time deiksis discourse and deiksis socially on a novel Sang Pemimpi created by Andrea Hirata. The research is qualitative study. Data collection method used is a technique read and write down. Data in this study of novel titled Sang Pemimpi created by Andrea Hirata. Analysis technique is using a technique deskriptf analysis. From the data analysis, deiksis in a novel Sang Pemimpi. Persona deiksis having six part including; the first single pronouns (i), the second person single pronouns (you), demonstrative the third person singular (he), pronouns (we first plural, we), second plural pronouns (you), third plural pronouns (they). Deiksis place found in this experiment in which; here, there, in the market. Deiksis time found in the study of them now, now, last, first. Deiksis discourse found of them anaphora and katafora. While social deiksis found in the study is among them mrs, and b.a.